Estudo tipológico dos cossoiros do Museu da Sociedade Martins Sarmento (Citânia de Briteiros, Castro de Sabroso e proveniência diversa) - Silva, Maria de Fátima (2018)
ABSTRACT: The present work is part of a wider project studying the characteristics, manufacture, decoration and raw-material, studying, in short, the part played by the “cossoiros” in the so called “textile economy” and in the society of several villages (“castros”) located by lhe sea as well as in lhe interior part of the region called “Entre Douro e Minho”. Through lhe study of the “cossoiros” coming from the hill fort of Briteiros in Guimarães, from the “Castro” of Sabroso and from other places, in a total of 221 pieces, it became possible to draw some conclusions that are now rendered public.